Morphologies, optical and electrical characterization of aluminum tin sulfide thin film - Muhamad Faiz Hashim, 1988- author 501419 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains, Pengkhususan : Fizik)